Cognitive and Emotional Reactions to Questions in the Comparison Question Test. Issue 2 (April 2014) - MacNeill, A. Luke; Bradley, M. T.; Cullen, M. C.; Arsenault, Andrea M.
The effect of situational factors on perceptions of items on the polygraph Comparison Question Test (CQT) was assessed. In an initial experiment, 86 students (30 men, 56 women; M age = 20.3 yr., SD = 4.0) imagined one of eight scenarios that varied by guilt or innocence, the commission of a real crime or mock crime, and interrogation by a police officer or a professor. They then rated generic CQT questions for importance and emotional concern. All participants rated crime-relevant questions as being more important than past-crime comparison questions. "Guilty" participants also rated these questions as being more emotionally concerning, but "innocent" participants showed no differences in their ratings of concern for the two question types. Interrogator or crime type did not affect the general pattern of responding. A second experiment involving 80 students (21 men, 58 women, 1 non-specified; M age = 22.5 yr., SD = 7.3) replaced the generic CQT questions with content-specific questions developed by the participant. Those imagining guilt showed no differences in their ratings of relevant and comparison questions, whereas those imagining innocence rated comparison questions as more concerning. Again, interrogator type and crime type had little effect on results. Overall, these findings indicated distinctions in cognitive and emotional appraisal for CQT questions, with the nature of emotional concern dependent on guilt/innocence status and the personal relevance of comparison questions. Evidence suggests that the CQT is robust to other situational factors, such as crime type and interrogator type.